Tradisi Tepung Tawar: Akulturasi Islam Dan Budaya Melayu Dalam Prosesi Pernikahan Masyarakat Melayu Di Kota Tanjung Balai - Nuraini Pangaribuan (Tamaddun: Jurnal Kebudayaan dan Sastra Islam, 2023)
The Tepung Tawar tradition is a tradition found in the series of wedding processions of the Malay community in Tanjung Balai City. This tradition is classified as a sacred tradition by the local community so it is still practiced today. This article aims to examine the process of implementing the Tepung Tawar tradition and analyze the forms of religious and cultural acculturation that exist in this tradition. This research is descriptive qualitative research and the data collection process was carried out by the author by means of observation, interviews and documentation as well as literature review. The results of this research show that initially this tradition was a ritual originating from Hindu beliefs which then experienced acculturation with Malay culture. This statement is strengthened by the similarities between the Tepung Tawar tradition and traditional Indian (Hindu) wedding rituals. Apart from that, historical facts reveal that the arrival of foreign nations, one of which was Indians (Hindus) to Malay land in the 7th or 8th century AD was the forerunner to the development of Hindu culture in Malay land, especially Tanjung Balai City, so that it was very dominant for affect the welfare of local communities. However, after Islam was introduced, Tepung Tawar became a tradition of the Malay community in which Islamic religious teachings were inserted. So this research can be concluded that Tepung Tawar is a form of religious and cultural acculturation that occurs in the Malay community in Tanjung Balai City, as well as a means of requesting blessings and peace to Allah SWT for people in Tepung Tawari.